Intra-axonal mechanisms driving axon regeneration - Smith, Terika P. (Brain Res, 2020)
Traumatic injury to the peripheral and central nervous systems very often causes axotomy, where an axon loses connections with its target resulting in loss of function. The axon segments distal to the injury site lose connection with the cell body and degenerate. Axotomized neurons in the periphery can spontaneously mount a regenerative response and reconnect to their denervated target tissues, though this is rarely complete in humans. In contrast, spontaneous regeneration rarely occurs after axotomy in the spinal cord and brain. Here, we concentrate on the mechanisms underlying this spontaneous regeneration in the peripheral nervous system, focusing on events initiated from the axon that support regenerative growth. We contrast this with what is known for axonal injury responses in the central nervous system. Considering the neuropathy focus of this special issue, we further draw parallels and distinctions between the injury-response mechanisms that initiate regenerative gene expression programs and those that are known to trigger axon degeneration.